2015
DOI: 10.1155/2015/434039
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Gastric Intestinal Metaplasia and Distribution ofHelicobacter pyloriInfection, Atrophy, Dysplasia, and Cancer in Its Subtypes

Abstract: Objectives. Gastric intestinal metaplasia (IM) is frequently encountered and is considered a precursor of gastric adenocarcinoma. In the Van region of Turkey, gastric adenocarcinoma incidence is high but the prevalence of gastric IM is not known. Helicobacter pylori (H. pylori) infection is a main factor leading to atrophy, IM, and cancer development in the stomach. The aim of the current study was to investigate the prevalence of IM and its subtypes and the prevalence of H. pylori infection, atrophy, dysplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 33 publications
2
29
4
1
Order By: Relevance
“…In the presence of H. pylori, the prevalence of atrophy was 2.5 times higher (17.6 vs 6.9%) and metaplasia was 1.3 times higher (17.7 vs 13.3%) compared to H. pylori (-) patients. These results are in accordance with several studies (16,(33)(34)(35) and also with the findings of the meta-analysis mentioned above in which the prevalence of the atrophy was 2.7 times higher and metaplasia was 2.1 times higher in individuals infected by H. pylori than in uninfected individuals (30) . In the current study the percentage difference between H. pylori (+) and H. pylori (-) patients was higher in atrophy than in metaplasia.…”
Section: Discussionsupporting
confidence: 93%
“…In the presence of H. pylori, the prevalence of atrophy was 2.5 times higher (17.6 vs 6.9%) and metaplasia was 1.3 times higher (17.7 vs 13.3%) compared to H. pylori (-) patients. These results are in accordance with several studies (16,(33)(34)(35) and also with the findings of the meta-analysis mentioned above in which the prevalence of the atrophy was 2.7 times higher and metaplasia was 2.1 times higher in individuals infected by H. pylori than in uninfected individuals (30) . In the current study the percentage difference between H. pylori (+) and H. pylori (-) patients was higher in atrophy than in metaplasia.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, CAG was significantly associated with H. pylori, and is a good suggestion for the causative role of H. pylori in chronic active gastritis. Many clinical studies reported that H. pylori is significantly associated with CAG, atrophic gastritis, intestinal metaplasia and gastric cancer ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection is a main factor leading to atrophy, intestinal metaplasia, and cancer development in the stomach [ 23 ]. In the present study, 512 patients with gastric cancer had been checked for the presence of H. pylori.…”
Section: Resultsmentioning
confidence: 99%